MEMBANGUN DISIPLIN DAN SPIRITUALITAS PESERTA DIDIK MELALUI PENDIDIKAN AGAMA KRISTEN BERBASIS TEOLOGI PRAKTIS - Seliaty Tiku Lempan; Risma Toding Allo, Lusiana, Delti Limbong Tiboyong; Yusmaliani (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This article discusses the strategic role of Christian Religious Education (PAK) based on practical theology in shaping students' discipline and spirituality amidst the current of globalization and moral crisis. Religious education is not only understood as doctrinal teaching, but as a process of life transformation that touches on cognitive, affective, and conative dimensions. This study uses a qualitative approach with a library study method, analyzing various theological and Christian education literature, as well as observational data from learning practices in Christian schools. The results of the study show that the integration of faith values into the curriculum, school culture, and teacher role models can foster discipline as a form of spiritual awareness, not just formal obedience. Meanwhile, students' spirituality is built through a personal relationship with God expressed in prayer, worship, service, and social ethics. Practical theology becomes a bridge between faith and everyday life, helping students actualize Christian teachings in real terms. The conclusion of this article emphasizes that the implementation of PAK based on practical theology is very relevant and urgent to create a generation that is strong in faith, character, and social responsibility. The contribution of this research is expected to be a reference for Christian schools in building an educational ecosystem that humanizes the whole.